The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.2514/1.13024
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Application of Eddy Current Damper for Suppression of Membrane Vibrations

Abstract: Inflatable space-based structures have become increasingly popular over the past three decades due to their minimal deployed mass and launch volume. To facilitate packaging of the satellite in the shuttle bay, the optical or antenna surface is in many cases a thin-film membrane. Additionally, because the structure holding the membrane is a lightweight and flexible inflated device, the membrane is subjected to a variety of dynamic loadings. For the satellite to perform optimally, the membrane structure must be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…This concept used the magnet's axial flux induced by two oppositely poled magnets and has been studied by previous researchers [1][2][3][4] because of the desirable traits that this method has for magnetic braking. Sodano et al [16][17][18] proposed a new concept using the eddy currents induced in a conductive plate which oscillates through the magnetic poling axis as shown in Fig. 1(b).…”
Section: Introductionmentioning
confidence: 98%
“…This concept used the magnet's axial flux induced by two oppositely poled magnets and has been studied by previous researchers [1][2][3][4] because of the desirable traits that this method has for magnetic braking. Sodano et al [16][17][18] proposed a new concept using the eddy currents induced in a conductive plate which oscillates through the magnetic poling axis as shown in Fig. 1(b).…”
Section: Introductionmentioning
confidence: 98%
“…While this configuration is effective for magnetic damping, it is not functional for use as an actuator for providing dynamic energy to a structure. However, Sodano et al [11,12] recently developed an eddy current damping scheme that functioned such that forces were generated in the poling axis of the magnet rather than perpendicular to it as previous studies had done. The study modeled and experimentally demonstrated the placement of a permanent magnet in close proximity to a conductive structure vibrating along the poling axis of the magnet could induce damping levels as high as 35% of critical.…”
mentioning
confidence: 95%
“…Therefore the damping system developed by Sodano et al [11][12][13] can be modified to allow the permanent magnet to move relative to the structure such that forces are generated due to the motion of the magnet relative to the beam. The proposed eddy current excitation system will convert a traditional linear actuator into a non-contact actuator.…”
mentioning
confidence: 99%
“…The concept of the ECD used in the present study is presented in Figure 4 and is proposed by Sodano et al [14][15][16] and Bae et al [10]. The damping force ( ) in the (vertical) direction due to the eddy current in Figure 4 yields…”
Section: Modeling Of Eddy Current Dampingmentioning
confidence: 99%
“…Using this model, they have investigated the ECD damping characteristics and performed the simulation of the vibration suppression of a cantilever beam with Kwak's ECD. Sodano et al [14][15][16] proposed the new concept of ECD device to attenuate the vibration of a cantilevered beam. Cheng and Oh [17,18] studied multimode vibration suppression using a permanent magnet and a coil with a shunt circuit for semiactive control.…”
Section: Introductionmentioning
confidence: 99%